1975
DOI: 10.1002/aic.690210404
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur dioxide oxidation in slurries of activated carbon. Part I. Kinetics

Abstract: Part 1. KineticsDynamic adsorption and reaction studies were made for the catalytic oxidation of sulfur dioxide in aqueous slurries of activated carbon at room temperature and atmospheric pressure. For the small particles (d, = 0.03 mm) of carbon used, mass transfer resistances were of minor importance SO that the data could be analyzed in terms of the kinetics of the chemical reaction. Quantitative evaluation of mass transfer effects, including intraparticle diffusion, is presented in Part 11.The rate was fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 8 publications
2
37
0
Order By: Relevance
“…The experimental data of Komiyama and Smith (1975b) for oxidation of sulfur dioxide in a slurry reactor provide a means for testing some of the results of the preceding section. These authors measured rates of reaction RA as a function of catalyst loading M , and particle diameter for semibatch operation, that is, continuous gas flow but no flow of liquid.…”
Section: Slurry Reactors: No Liquid Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental data of Komiyama and Smith (1975b) for oxidation of sulfur dioxide in a slurry reactor provide a means for testing some of the results of the preceding section. These authors measured rates of reaction RA as a function of catalyst loading M , and particle diameter for semibatch operation, that is, continuous gas flow but no flow of liquid.…”
Section: Slurry Reactors: No Liquid Flowmentioning
confidence: 99%
“…The boundary conditions, Equation ( 7) , become Equations (23) to (26) are applicable to any reaction of the form of Equation (1) for which the kinetics are first oruer in A and zero oruer in B, Por s u h r dioxide oxidation with an activated carbon catalyst in an aqueous slurry (Komiyama, 1975a), the reaction was zero order because Cbsoz was in excess. In this case, y s B > 0.…”
Section: Mass Balance Equations For Reactants a And B Andmentioning
confidence: 99%
“…From the values of K and H at 5"C, kads is 0.32 cm3/ Komiyama and Smith (1975) in their study of the oxidation of sulfur dioxide, using a slurry of the same activated carbon particles as catalyst, concluded that the rate of adsorption of oxygen controlled the oxidation rate. If we assume that their rate of reaction is equal to the rate of oxygen adsorption, a value of kads = 2.25 cm3/(g) (s) is obtained at 25°C.…”
Section: Adsorption Ratementioning
confidence: 99%
“…Sci., A method has recentIy been deveIoped (Niiyama and Smith, 1976) for evaluating mass transfer and adsorption rates in three-phase slurry reactors by analyzing breakthrough curves in the effluent gas stream. Since slurry systems have been proposed for removing pollutants by oxidation with gaseous oxygen, and since the rate of oxygen adsorption can significantly influence the rate of oxidation (Komiyama and Smith, 1975), we have used the new Hiroo Niiyama is on leave from Tokyo Institute of Technology, Japan. method to determine mass transport and intrinsic adsorption rate parameters for oxygen in aqueous slurries of carbon particles.…”
mentioning
confidence: 99%
“…Henry's law constant, H i s small (H = 0.01 21 at 298OC according to Komiyama and Smith, 1975) for the very soluble SO2 gas in water. Because the diffusivity in the gas phase is about lo4 times that in the liquid phase, k, is expected to be about lo2 times k,.…”
Section: Theorymentioning
confidence: 99%